Modelling of tick borne enecephalitis virus (TBEV) proteins and their complexes - Halbeisen, Marco (Jihočeská univerzita, 2022)
In this bachelor thesis the focus was on the study of non-structural proteins of the tick-borne encephalitis virus involved in the replicatory process of the virus. Non-structural protein number 3 (NS3) and number 5 (NS5) contain a helicase and an RNA-dependent RNA polymerase domain, respectively, and play a crucial role in the life cycle of the virus. Therefore, they are of interest to develop a potential antiviral drug inhibiting the replication of the pathogen. It has been found that these two proteins form a dimer during the replication of the viral RNA. The aim of the thesis was to identify the exact interaction of the two proteins with existing hydrogen-deuterium mass spectroscopy data as well as modelling the RNA into the complexes. The research was conducted by using computational biology tools including homology modelling using MODELLER, manual modelling in PyMOL and Chimera as well as Molecular Dynamics Simulations in GROMACS.
Modelling of tick borne enecephalitis virus (TBEV) proteins and their complexes
Keywords: PyMOL; Homology modelling; Molecular dynamics simulation; site directed mutagenesis; PyMOL; Homology modelling; Molecular dynamics simulation; site directed mutagenesis